Treatment of renal failure in neonates. Issue 11 (November 1988) - Meeks, A C; Sims, D G
Abstract : Thirty neonates with acute renal failure were studied, 27 of whom died (90%) including nine of 12 treated by peritoneal dialysis. Three main aetiological groups were identified. Septicaemia was a principal cause of late onset acute renal failure, with an incidence equal to that of serious perinatal disorders. It is recommended that tolazoline should be used with caution in the treatment of hyperkalaemia as it may have a role in the aetiology of acute renal failure, the incidence of which is increasing.